'I used to be a gardener': Connecting aged care residents to gardening and to each other through communal garden sites. (3rd September 2020) - Fielder, Hannah; Marsh, Pauline
Abstract: Objective: To explore residential aged care facility (RACF) residents' use of communal garden sites as spaces for gardening and social connection. Methods: Phenomenological inquiry using semi‐structured interviews with 13 residents, family members and staff of a rural RACF. Results: Interest, ability and willingness to engage in communal garden sites were evident but limited by multiple factors. Data highlighted the complexities of accessing gardens, gardening and other people. An enduring identity as a gardener provided a framework for maintaining a link between gardening, finding meaning and maintaining a sense of self. Conclusion: Communal garden sites can improve quality of life and enable connectedness for RACF residents. However, a range of personal, attitudinal, institutional and resource‐related challenges create barriers to gardening, and in the RACF isolation and inactivity persist. We conclude that these challenges might be overcome through provision of physical and emotional support for positive risk‐taking, autonomy and access to the outside to continue gardening.